Susceptibility of Haemophilus influenzae Type b to Cefatrizine, Ampicillin, and Chloramphenicol - Brotherton, Thomas (1976)
The susceptibility of 269 isolates of Haemophilus influenzae type b to cefatrizine (BL-S640), ampicillin, and chloramphenicol was evaluated by disk diffusion susceptibility tests, using a modified Bauer-Kirby method. Broth dilution susceptibility tests were performed on 88 of these isolates, including all isolates resistant by disk to cefatrizine or ampicillin. Six of the isolates were resistant by disk to cefatrizine (zone size, <16 mm), four were resistant to ampicillin (zone size, <19 mm), and none were resistant to chloramphenicol (zone size, <17 mm). Only two of the six isolates of H. influenzae that were resistant to cefatrizine by disk were resistant to more than 4 μg of drug per ml. The four organisms resistant to ampicillin on disk were resistant, when tested by the broth method, to >128 μg/ml. These four ampicillin-resistant H. influenzae were susceptible to <4 μg of cefatrizine per ml. The two isolates resistant to >4 μg of cefatrizine per ml were susceptible to 0.5 and 2 μg of ampicillin, respectively, per ml. The activity of cefatrizine appears to be comparable in vitro to ampicillin against H. influenzae.